Physical Activity and Oxidative Stress in Aging - Rosamaria Militello; Simone Luti; Tania Gamberi; Alessio Pellegrino; Alessandra Modesti; Pietro Amedeo Modesti (MDPI AG, 2024)
Biological aging, characterized by changes in metabolism and physicochemical properties of cells, has an impact on public health. Environment and lifestyle, including factors like diet and physical activity, seem to play a key role in healthy aging. Several studies have shown that regular physical activity can enhance antioxidant defense mechanisms, including the activity of enzymes such as superoxide dismutase (SOD), catalase, and glutathione peroxidase. However, intense or prolonged exercise can also lead to an increase in reactive oxygen species (ROS) production temporarily, resulting in oxidative stress. This phenomenon is referred to as "exercise-induced oxidative stress". The relationship between physical activity and oxidative stress in aging is complex and depends on various factors such as the type, intensity, duration, and frequency of exercise, as well as individual differences in antioxidant capacity and adaptation to exercise. In this review, we analyzed what is reported by several authors regarding the role of physical activity on oxidative stress in the aging process as well as the role of hormesis and physical exercise as tools for the prevention and treatment of sarcopenia, an aging-related disease. Finally, we reported what has recently been studied in relation to the effect of physical activity and sport on aging in women.